Prognostic relevance of rib invasion and modification of T description for resected NSCLC patients: A propensity score matching analysis of the SEER database - Chen, Yiyong; Zhang, Juan; Chen, Jing; Yang, Zijie; Ding, Yun; Chen, Wenshu; Guo, Tianxing; Zhao, Lilan; Pan, Xiaojie (Frontiers in Oncology, 2023)
Introduction: The impact of rib invasion on the non-small cell lung cancer (NSCLC) T classifications remains unclear. Our study aims to verify the impact of rib invasion on survival in patients with NSCLC through multicenter data from the Surveillance, Epidemiology, and End Results (SEER) database, and proposed a more appropriate pT for the forthcoming 9th tumor-node-metastasis (TNM) classifications. Method: The SEER database was used to collect T2b-4N0-2M0 NSCLC cases from the period of 2010-2015 according to the 7th TNM classification system. Subsequently, the T classification was restaged according to the 8th TNM classification system based on the following codes: pathological size and tumor extension. Cases with T1-2 disease and incomplete clinicopathological information were excluded. Finally, 6479 T3 and T4 NSCLC patients were included in the present study and divided into a rib invasion group (n = 131), other pT3 group (n = 3835), and pT4 group (n = 2513). Propensity-score matching (PSM) balanced the known confounders of the prognosis, resulting in two sets (rib invasion vs. other pT3 and pT4 group). Overall survival (OS) and cancer-specific survival (CSS) were investigated using Kaplan-Meier survival curves, and predictive factors of OS and CSS were assessed by Cox regression. Result: Survival outcomes of the rib invasion group were worse than the other pT3 group (OS: 40.5% vs. 46.5%, p = 0.035; CSS: 49.2% vs. 55.5%, p = 0.047), but comparable to the pT4 group (OS: 40.5% vs. 39.9%, p = 0.876; CSS: 49.2% vs. 46.3%, p = 0.659). Similar results were obtained after PSM. Multivariate analyses for all patients revealed that age at diagnosis, gender, pathological N stage, T stage, surgical modalities, and adjuvant therapy had a predictive value for the prognosis. Conclusion: The rib invasion group had a worse prognosis than the other pT3 groups, but was similar to the pT4 group. Our recommendation is to change the reclassified rib invasion to pT4 disease and further validate this in the forthcoming 9th TNM classification.